2022
DOI: 10.1002/cam4.5178
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pyroptosis‐based model for predicting clinical outcomes from immunotherapy in patients with metastatic melanoma

Abstract: Immunotherapy has greatly improved outcomes for patients with advanced melanoma, but good predictive biomarkers remain lacking in clinical practice. Although increasing evidence has revealed a vital role of pyroptosis in the tumor microenvironment (TME), it remains unclear for pyroptosis as a predictive biomarker for immunotherapy in melanoma. RNA sequencing data and annotated clinical information of melanoma patients were obtained from four published immunotherapy datasets. LASSO regression analysis was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In this study, we constructed the PScore model to evaluate pyroptosis status in melanoma patients, as there is as yet no applicable and quick method to estimate pyroptosis status other than electron microscopy or PCR [101][102][103]. Although some pyroptosis-related models based on RNA sequencing [104,105] have been explored to predict the clinical outcome of cutaneous melanoma patients, in-depth research is still lacking. We found that PRGs have different expression patterns in primary and metastatic tumors and that the NMF method based on PRGs can predict the prognosis of metastatic patients but not primary patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we constructed the PScore model to evaluate pyroptosis status in melanoma patients, as there is as yet no applicable and quick method to estimate pyroptosis status other than electron microscopy or PCR [101][102][103]. Although some pyroptosis-related models based on RNA sequencing [104,105] have been explored to predict the clinical outcome of cutaneous melanoma patients, in-depth research is still lacking. We found that PRGs have different expression patterns in primary and metastatic tumors and that the NMF method based on PRGs can predict the prognosis of metastatic patients but not primary patients.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several attempts thus far to establish prognostic models related to pyroptosis [19][20][21][22][23][24][25][26][27][28][29]. The majority of them have been built based on least absolute shrinkage and selection operator (LASSO) regression [30] with distinct gene sets as input.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Wu and colleagues, a PYR-based model was constructed by analyzing RNA sequencing data and clinical information of melanoma patients from four immunotherapy databases, including Gide (patients receiving anti-PD1 or the combination anti-PD1 and anti-CTLA4), Lauss (patients treated with adoptive T-cell therapy), Liu (patients treated with anti-PD1) and Nathanson (patients treated with anti-CTLA4) [ 101 ]. Gide worked as the training cohort and the others as validation cohorts.…”
Section: Pyroptosis and Cancermentioning
confidence: 99%